Open In App

Proof of De-Morgan’s laws in boolean algebra

Last Updated : 21 Sep, 2023
Improve
Improve
Like Article
Like
Save
Share
Report

Statements :

1.

(x+y)'= x'. y'

2.

(x.y)'=x'+y'

Proof:

Here we can see that we need to prove that the two propositions are complement to each other. We know that

A+A'=1

and

A.A'=0

which are annihilation laws. Thus if we prove these conditions for the above statements of the laws then we shall prove that they are complement of each other.

For statement 1:

We need to prove that:

(x+y)+x'.y'=1

and

(x'.y').(x+y)=0

Case 1.

 (x+y)+x'.y'=1    [Tex]LHS: (x+y)+x’.y’ =(x+y).(x+x’)+x’.y’ [/Tex]=x.x+x.y+y.x'+x'.y'=x+x.y+y.x'+x'.y'

{Using distributive property}

=x+x.y+x'.(y+y')   [Tex]=x+x.y+x’=x+x’+x.y [/Tex] =1+x.y=1=RHS

Hence proved.

Case 2.

 (x'.y').(x+y)=0    [Tex]LHS: (x’.y’).(x+y)=x.(x’y’)+y.(x’.y’) [/Tex]=x.0+0.x'=0=RHS

Hence proved.

For statement 2:

We need to prove that:

x.y+(x'+y')=1

and

x.y.(x'+y')=0

Case 1.

x.y+(x'+y')=1   [Tex] LHS: x.y+(x’+y’)=(x+x’+y’).(y+x’+y’) [/Tex]

{We know that A+BC=(A+B).(A+C)}

=(1+y').(1+x')=1=RHS

Hence proved.

Case 2.

x.y.(x'+y')=0   [Tex]LHS: (x.y).(x’+y’)=x.x’.y+x.y.y’ [/Tex]=0=RHS

Hence Proved. This proves the De-Morgan’s theorems using identities of Boolean Algebra.

Proof of De-Morgan’s law of boolean algebra using Truth Table:

1) (x+y)’= x’. y’

x

y

x+y

(x+y)’

x’

y’

x’. y’

0

0

0

1

1

1

1

0

1

1

0

1

0

0

1

0

1

0

0

1

0

1

1

1

0

0

0

0

Hence the first De-morgan law of boolean algebra is proved (x+y)’= x’. y’

2) (x.y)’=x’+y’

x

y

x.y

(x.y)’

x’

y’

x’+y’

0

0

0

1

1

1

1

0

1

0

1

1

0

1

1

0

0

1

0

1

1

1

1

1

0

0

0

0

Hence the second De-morgan law of boolean algebra is proved (x.y)’=x’+y’





Like Article
Suggest improvement
Previous
Next
Share your thoughts in the comments

Similar Reads